Construction of Cry1Ac Plasmid Vector and Its Transformation into Agrobacterium tumefaciens - Sri Koerniati; Alifah R. Heritiera (Jurnal AgroBiogen, 2014)
Introducing cry genesinto rice genome is reported able to produce rice plantresistant to stemborer. DNA sequence encodes cry1Ac genehas been inserted into pGEM4Z, but this construct does nothave a selectable marker gene for selection of transformedplant cells. The research aims were to construct a plasmidvector expressing a cry1Ac gene that has a transformationselectable gene and to transform it into Agrobacteriumtumefaciens. Materials used were pAY560325 binary plasmidvector, pGEM4Z-cry1Ac vector, Escherichia coli strain DH5-αand A. tumefaciens strain LBA4404 competent cells. Themethods consisted of plasmid DNA digestion using HindIIIand EcoRI, electrophoresis, DNA (backbone and insert)dissection from the gel, purification, and ligation using T4DNA ligase. Transformation of ligated DNA into E. coli byheat shock followed by cell plating onto selection medium,colony cultured, DNA isolation, and identification usingrestriction enzymes. Reconfirmation was done by cuttingusing restriction enzyme and PCR using F3 and R3, cry1Acgene specific primers. Research result were DNA fragmentsof 3.8 kb ubiquitin::cry1Ac insert and pAY560325, thebackbone vector, that after ligated and transformed into E.coli produced colonies. One of ten colonies containingplasmid DNA was evidently confirmed and namedpAY560325-cry1Ac. Subsequently, it was transformed into A.tumefaciens by electrophoration method. Plasmid DNA wasisolated from Agrobacterium that after digested with HindIIIand EcoRI produced DNA fragments of 9.44 kb (pAY560325)and 3.814 kb (ubiquitin::cry1Ac). While by PCR, plasmidproduced DNA fragment of about 711 bp. Thus, cry1Acplasmid vector (pAY560325-cry1Ac) was successfullyconstructed and transformed into A. tumefaciens and isready to be transformed into rice genome.